Bridging the Access Gap for Comprehensive Sickle Cell Disease Management Across Sub-Saharan Africa: Learnings for Other Global Health Interventions? - Lutz Hegemann; Vas Narasimhan; Kwaku Marfo; Patrick Kuma-Aboagye; Solomon Ofori-Acquah; Isaac Odame (Ubiquity Press, 2023)
Background: Sickle cell disease (SCD) is a major unresolved global health issue, with the highest disease burden in sub-Saharan African countries; yet, SCD care has not proportionally reached patients in these regions, and the disease has received limited attention in the past. Addressing the burden of SCD in sub-Saharan Africa requires a holistic, collaborative approach to ensure solutions are both comprehensive - i.e., cover the entire continuum of care from early diagnosis to treatment - and sustainable - i.e., are co-created and co-owned with local partners and integrated into existing local systems to enable long-term independence without the need for continuous external support. Objective: We outline a set of recommendations for enhancing the provision of comprehensive healthcare for prevalent diseases in resource-constraint settings, gathered from the Novartis Africa SCD Program, that could serve as 'blueprint' for public-private partnerships to tackle global health priorities. Methods: The Novartis Africa SCD program was initiated with the aim to bridge access gaps to SCD care and provide comprehensive and innovative treatment solutions for SCD, especially in SSA where the disease burden is highest. The Program was first inaugurated in 2019 in Ghana through a public-private partnership with the Ministry of Health of the Government of Ghana, the Ghana Health Service, and the Sickle Cell Foundation of Ghana. Through engagement with these partners, as well as with support from other organizations with complementary competencies and resources, several targeted solutions were implemented to help strengthen the healthcare ecosystem to allow for comprehensive SCD management. Learnings from these interventions are highlighted as best practice consideration as a catalyst and to activate more public-private actors for this neglected global health issue. Findings and Conclusions: A solid understanding of the access barriers to comprehensive care has to be acquired by listening to and learning from patients, civil society, and local experts. Access barriers need to be addressed at multiple levels, i.e., by not only making medicines available and affordable, but also by strengthening healthcare systems, building capacity, and fostering local research and development. Partnerships across governmental, public, academic, non-profit, and private organizations are needed to secure political will, pool resources, gather expertise with understanding of the local context, and allow integration into all levels of existing local healthcare structures and the wider society.